Development and Psychometric Evaluation of Nursing Audit Tool - Dilek Ekici; Tugba Mert (Baqiyatallah University of Medical Sciences, 2020)
Background: Better healthcare outcomes in health services are obtainable from frequently observing ongoing healthcare activities, gathering data, and assessing outcomes. Objectives: This study aimed to establish the basic principles of nursing care standards and practices in wards, develop a nursing audit tool for periodically monitoring and controlling ongoing nursing activities, and evaluate nursing care quality. Methods: A methodological investigation of field visit data gathered between November 2017 and April 2019 was conducted. A nursing service audit tool was used to collect data. Based on the literature and expert consideration, a conceptual structure of the nursing audit criteria containing 63 items and four factors (patient care, indirect care, unit criteria, and head nurse) was developed. The hospital supervisors visited all the wards and evaluated all the items of the tool accordingly. Nursing outcomes of units were used for determine the predictive validity of the tool. Two supervising nurses collected the data using the tool during their shifts. Supervisors were trained on the use of the tool to avoid any differences between evaluators. Each supervisor collected 309 tools. A total of 618 data were collected. Results: The level of validity and reliability of the tool is within acceptable limits; thus, it can be regarded as a valid and reliable tool for monitoring nursing care processes in the general wards of the hospital. Conclusion: The developed tool will help nurse managers monitor the nursing care process in accordance with the quality standards.